Blood and breath levels of selected volatile organic compounds in healthy volunteers - Mochalski, Paweł (Analyst, 2013)
Gas chromatography with mass spectrometric detection (GC-MS) was used to identify and quantify volatile organic compounds in the blood and breath of healthy individuals. Blood and breath volatiles were preconcentrated using headspace solid phase micro-extraction (HS-SPME) and needle trap devices (NTDs), respectively. The study involved a group of 28 healthy test subjects and resulted in the quantification of a total of 74 compounds in both types of samples. The concentrations of the species under study varied between 0.01 and 6700 nmol L(−1) in blood and between 0.02 and 2500 ppb in exhaled air. Limits of detection (LOD) ranged from 0.01 to 270 nmol L(−1) for blood compounds and from 0.01 to 0.7 ppb for breath species. Relative standard deviations for both measurement regimes varied from 1.5 to 14%. The predominant chemical classes among the compounds quantified were hydrocarbons (24), ketones (10), terpenes (8), heterocyclic compounds (7) and aromatic compounds (7). Twelve analytes were found to be highly present in both blood and exhaled air (with incidence rates higher than 80%) and for 32 species significant differences (Wilcoxon signed-rank test) between room air and exhaled breath were observed. By comparing blood, room air and breath levels in parallel, a tentative classification of volatiles into endogenous and exogenous compounds can be achieved.